Relationship between fear of COVID-19 and premenstrual syndrome in Turkish university students. (9th August 2022) - Kaplan, Sena; Gürler, Meryem; Gönenç, İ̇lknur Münevver
ABSTRACT: Premenstrual syndrome (PMS) has been reported to be related to psychological distress. The COVID-19 pandemic has globally caused heightened levels of stress, anxiety, and fear. There is no sufficient evidence regarding the impact of the fear of COVID-19 on PMS and related symptoms. Therefore, this study examined the association of the fear of COVID-19 with PMS among Turkish university students. The sample of this cross-sectional study consisted of 829 Turkish university students. Data were collected online using the Questionnaire Form, the Premenstrual Syndrome Scale (PMSS), and the Fear of COVID-19 Scale (FCoV-19S). The prevalence of PMS was 73 percent. The most common symptoms were fatigue, irritability, appetite changes, and depression. Participants had a moderate fear of COVID-19 (mean FCoV-19S: 20.48 ± 5.96). Most participants stated that the pandemic did not affect the menstrual cycle length (72.5 percent) and bleeding (79.6 percent). Participants who noted that the pandemic impacted the length of their menstrual cycles and bleeding had a significantly higher mean FCoV-19S score than those who did not ( p = .000). Moreover, FCoV-19S scores were positively correlated with PMS scores, PMS-related discomfort, and dysmenorrhea VAS scores ( p < .001). This study revealed that the fear of COVID-19 affected PMS and menstrual cycle-related symptoms in Turkish university students.